Do scoring techniques and number of choices affect the reliability of multiple-choice tests in elementary schools? - Herwin, Herwin; Pristiwaluyo, Triyanto; Ruslan, Ruslan; Dahalan, Shakila Che (Cypriot journal of educational sciences, 2022)
The application of multiple-choice tests often does not consider the scoring technique and the number of choices. The study aims at describing the effect of the scoring technique and numerous options towards the reliability of multiple-choice objective tests on social subjects in elementary school. The study is quantitative research with experiments using factorial design. The population of the study was all the items of the standard of multiple-choice objective test through the test development procedure. The sample of the study was part of the items taken randomly through repeated simulations. Data collection was participants’ scores taken from the test and repeated simulations 120 times for the analysis. Data were analysed in descriptive quantitative and inferential through the analysis of variance. The results of the study reveal that there is an interaction between scoring technique and numerous options towards the reliability of multiple-choice objective tests on social subjects in elementary school.